The art of being together: a social constructionist perspective on dialogic methods in the organizational context - Aguiar, Ana Carolina Pires de (2016)
The purpose of this project is to understand, under a social constructionist approach, what are the meanings that external facilitators and organizational members (sponsors) working with dialogic methods place on themselves and their work. Dialogic methods, with the objective of engaging groups in flows of conversations to envisage and co-create their own future, are growing fast within organizations as a means to achieve collective change. Sharing constructionist ideas about the possibility of multiple realities and language as constitutive of such realities, dialogue has turned into a promising way for transformation, especially in a macro context of constant change and increasing complexity, where traditional structures, relationships and forms of work are questioned. Research on the topic has mostly focused on specific methods or applications, with few attempts to study it in a broader sense. Also, despite the fact that dialogic methods work on the assumption that realities are socially constructed, few studies approach the topic from a social constructionist perspective, as a research methodology per se. Thus, while most existing research aims at explaining whether or how particular methods meet particular results, my intention is to explore the meanings sustaining these new forms of organizational practice. Data was collected through semi-structured interviews with 25 people working with dialogic methods: 11 facilitators and 14 sponsors, from 8 different organizations in Brazil. Firstly, the research findings indicate several contextual elements that seem to sustain the choices for dialogic methods. Within this context, there does not seem to be a clear or specific demand for dialogic methods, but a set of different motivations, objectives and focuses, bringing about several contrasts in the way participants name, describe and explain their experiences with such methods, including tensions on power relations, knowledge creation, identity and communication. Secondly, some central ideas or images were identified within such contrasts, pointing at both directions: dialogic methods as opportunities for the creation of new organizational realities (with images of a ‘door’ or a ‘flow’, for instance, which suggest that dialogic methods may open up the access to other perspectives and the creation of new realities); and dialogic methods as new instrumental mechanisms that seem to reproduce the traditional and non-dialogical forms of work and relationship. The individualistic tradition and its tendency for rational schematism - pointed out by social constructionist scholars as strong traditions in our Western Culture - could be observed in some participants’ accounts with the image of dialogic methods as a ‘gym’, for instance, in which dialogical – and idealized –‘abilities’ could be taught and trained, turning dialogue into a tool, rather than a means for transformation. As a conclusion, I discuss what the implications of such taken-for-granted assumptions may be, and offer some insights into dialogue (and dialogic methods) as ‘the art of being together’.